IRON TABLETS DISTRIBUTION OF PREGNANT WOMAN IN THE DISTRICT AND CITY OF EAST JAVA PROVINCE - Soenarnatalina Melaniani (UPT Penerbitan Universitas Jember)
According to WHO (2008), Maternal Mortality Rate(MMR) is one success indicator of health servicesin a country. Maternal death can occur due toseveral reasons, such as anemia. Iron deficiency isa major cause of anemia in pregnant womencompared with a deficiency of other nutrients.Anemia is a health problem experienced by womenaround the world, especially in developingcountries.World Health Organization (WHO) reported thatthe prevalence of pregnant women who have irondeficiency is around 35-75% and thus increase inaccordance of the gestation. According to theWHO, 40% of maternal deaths in developingcountries are associated with anemia in pregnancyand most of anemia in pregnancy is caused by irondeficiency and acute bleeding, or both.Riskesdas data in 2013 indicate that there are25.3% of the total number of pregnant women inEast Java or around 24 people pregnant womensuffer from iron deficiency anemia duringpregnancy. The health of pregnant women need tobe improved in order to achieve the fifth MDGs, itshould be highly considered about the distributionof Fe tablets 30 and tablets 90, as well as the K1and K4 visit by pregnant women.Distribution of Fe tablet 30 and tablets 90 indistrics and cities need to be compared using thestatistic test namely T-test while to find the effectof tablet Fe 30 tablets in the K1 pregnancy visit andthe effect of tablet Fe 90 tablets in K4 pregnancyvisit by using regression.Research purposes :1. To analyze the differences between distributionof Fe tablets 30 and Fe tablets 90 ini districs andcities.2. To analyze the effect of Fe tablets 30 in K1pregnancy visit and the effect of the Fe tablets 90in K4 pregnancy visit, also its effectiveness in EastJava Province.Benefits of the research :Improve maternal health with the equality on thedistribution of Fe tablets 30 and Fe tablets 90 ineach districs and cities.